Air Pollution and Lung Cancer: A Deep Dive into the Impact in Southern India - Atul Khajuria; Eric Kwasi Elliason; Stephen Monday; J. Samuel Kamanda (International Journal of Toxins and Toxics, 2025)
Lung cancer incidence is rising in Southern India, with air pollution, particularly PM2.5, emerging as a significant risk factor alongside smoking. A retrospective cohort study analyzed data from 1,500 lung cancer patients diagnosed between 2010–2020 across Chennai, Bangalore, and Hyderabad, using hospital records, cancer registries, and environmental monitoring stations. The study found that 73.3% of patients were male, 80.7% were smokers, and 42.7% were aged 60+. Chennai had the highest PM2.5 levels (75.5 µg/m³) and lung cancer incidence (33.5%), with a strong correlation (r = 0.92, p
Keywords: Air pollution; Lung cancer; PM2.5; Southern India; smoking; survival analysis